Leather tanning sludge in cement mortar: Sustainable valorisation - Martins, Ramiro (2024)
This study aims to investigate the valorisation of sludge from Leather Tannery Wastewater Treatment Plants (LTWWTP) by incorporating it into cement mortars. Theoretical framework: The substantial quantity of waste generated by industries coupled with the scarcity of natural resources calls for the analysis, development, and implementation of treatment methods to recover and reuse materials, thereby minimising the environmental impact of waste disposal. The leather tanning industry, a significant polluter due to its use of hazardous and heavy materials, requires sustainable solutions for waste management. One promising approach is the incorporation of waste into cementitious matrices. Method: Three scenarios were examined: low-moisture sludge, ash obtained via incineration, and wet oxidation. Test specimens were prepared with varying proportions of cement replacement (0, 3, 5, 7, and 10%), and their flexural and compressive strengths were evaluated. Additionally, chemical analyses were conducted to assess solubility. Results and Conclusion: The results indicate that sludge can be used in small proportions without compromising the mechanical strength of the mortar. Substituting 10% cement with ash using the INC-2 incineration method improved mortar quality, exhibiting a higher compressive strength of 41 MPa and minimal water absorption (3.28%). Research implications: Drawing from these promising findings, it can be confidently asserted that utilising WWTP sludge in mortar is a practical, eco-conscious solution for civil construction. Furthermore, it is a pivotal step towards addressing the challenge of hazardous sludge disposal. Originality/value: The findings from this research will contribute to sustainable waste management practices and pave the way for responsible and eco-friendly utilisation of industrial waste in cementitious materials, thus minimising environmental burdens.